2019
DOI: 10.7150/ijms.33979
|View full text |Cite
|
Sign up to set email alerts
|

SiRNA-Mediated RRM2 Gene Silencing Combined with Cisplatin in the Treatment of Epithelial Ovarian Cancer In Vivo: An Experimental Study of Nude Mice

Abstract: Introduction: We aimed to explore small interfering (si)RNA silencing of ribonucleotide reductase M2 (RRM2) gene combined with cisplatin for the treatment of human ovarian cancer in nude mice models of subcutaneous transplantation of tumor cells.Methods: After conventional cultivation of human ovarian cancer cell line SKOV3 in vitro, SKOV3 cells were injected into the right back of nude mice by subcutaneous injection to establish the subcutaneous tumor models. Twenty-four tumor-burdened rats were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Overall, CP induces DNA damage in cancer cells and suppresses cancer cell proliferation and viability. The combination of CP with other chemotherapeutic agents has shown great potential in cancer therapy [49][50][51][52][53][54].…”
Section: Cisplatin In Cancer Therapymentioning
confidence: 99%
“…Overall, CP induces DNA damage in cancer cells and suppresses cancer cell proliferation and viability. The combination of CP with other chemotherapeutic agents has shown great potential in cancer therapy [49][50][51][52][53][54].…”
Section: Cisplatin In Cancer Therapymentioning
confidence: 99%
“…[ 40 ] Other studies have found that the combination of RRM2 knockdown and cisplatin is synergistic in mouse models. [ 94 ] Similarly, inhibition of folate synthesis via methotrexate or berberine reduces the viability of platinum‐resistant ovarian cancer cells. [ 95 ] While many of the classical anti‐metabolites have failed in clinical trials due to on‐target toxicity, advances in the understanding of nucleotide synthesis [ 96 ] may provide new opportunities to revisit inhibition of this pathways to exacerbate DNA damage‐inducing agents.…”
Section: Metabolism and Dna Repair In Ovarian Cancermentioning
confidence: 99%
“…In ovarian cancer cells, silencing of RRM2 via siRNA induces DNA damage and inhibits their repair. This, in turn, increases the sensitivity of cancer cells to cisplatin chemotherapy …”
Section: Sirna: Basics Role In Anticancer Therapy Challenges and Poss...mentioning
confidence: 99%
“…This, in turn, increases the sensitivity of cancer cells to cisplatin chemotherapy. 94 The signaling networks responsible for proliferation, metastasis, radioresistance and chemoresistance of cancer cells have been reported in previous studies. Targeting molecular pathways is important in suppressing the aggressive behavior of cancer cells and in promoting their responses to chemotherapy and radiotherapy.…”
Section: ■ Introductionmentioning
confidence: 99%